Análisis Comparativo de las Técnicas de Series de Tiempo Arima y Anfis para Pronosticar Tráfico Wimax - Salcedo Parra, Octavio José; Hernández Suárez, César Augusto; Pedraza Martínez, Luis Fernando (Ingeniería, 2006)
This paper presents the procedure and the main result of a comparative study based on the used of a autoregressive model and a technique artificial intelligence applied to the ask of predicting a series of traffic data Wimax. The prediction methods of time series compared are: the ANFIS model (Adaptative Network based Fuzzy Inteference System) and the ARIMA model (autoregressive integrated moving average).The goal of this article is to article is to present significant data showing the performance of each of the above techniques at the discretion of the shape of the root mean square error and time-processing required. As a resultsof this study, are compared the models ARIMA development under the software MATLAB.